Effects of roasted coffee on the chemical, microbiological and sensory qualities of fermented cocoa and cashew juices. Issue 6 (27th January 2021) - Gyedu-Akoto, Esther; Kumi Asare, Eric; Opoku, Stephen Yaw; Dadzie, Abu Mustapha; Ofosu-Agyei, Emmanuel
Abstract : Purpose: Roasted coffee provides a complex blend of different flavours which produce a range of sensory qualities. With the development of protocols for the production of fresh juices, jams and marmalades from cocoa and cashew pulp juices at Cocoa Research Institute of Ghana, this paper aims to study the effects of roasted coffee powder on fermented cocoa and cashew juices to diversify the uses of these two juices. Design/methodology/approach: Cocoa and cashew juices were fermented with the incorporation of 2% roasted coffee powder using Saccharomyces cerevisiae yeast starter. The fermenting juices were monitored by measuring pH, temperature, specific gravity and titratable acidity. At the end of the fermentation, the juices were poured into clean, sterilized containers to mature. They were then analysed for their physicochemical, microbiological and sensory qualities. These were repeated with cocoa and cashew juices without coffee powder to determine the effects of the roasted coffee on the fermented juices. Findings: The addition of roasted coffee powder to cocoa and cashew juices did not have any significant effect on the fermentation performance of the juices. Three out of the four juices took a total of 13 days to complete fermentation with an average final specific gravity of 0.99. The quality of the fermented juices was not compromised by microbial activities. However, the addition of roasted coffee powder reduced the alcohol content of fermented cocoa juice from 9.0 to 5.0% and that of cashew from 11.0% to 7.5%. Sensory analysis using untrained panellists, who were ordinary consumers, showed significant differences among the four fermented juices in terms of appearance, taste and aroma. Their mean scores for coffee aroma ranged from 0.3 to 2.0 with coffee incorporated fermented juices having higher rankings. Originality/value: These findings have shown the possibility of processing cocoa and cashew juices, which under normal circumstances would have been discarded along their value chains, into coffee-flavoured wines. They are also important to cocoa, cashew and coffee farmers, processors, as well as wine enthusiasts.